Documents on the Introduction of the Maritime Command Flag, 1984–85 - Bertosa, Brian (The Northern Mariner / Le marin du nord, 2025)
The sea element of the Canadian Armed Forces was allowed to enter the unification era with a distinctive flag, the Canadian Armed Forces Naval Jack of 1968. It was the only one of the three elements granted this privilege. Two decades on, increasing signs of separate environmental or “service” identities were emerging in the unified force. In 1984, the Commander of Maritime Command asked to have the Jack renamed and flown ashore as a command flag and in HMC Ships as the ensign. Through a close examination of four key documents associated with the episode, this commentary explores the request in detail, as well as the reaction to it on the part of the Chief of the Defence Staff, a staunch unificationist. In so doing, it serves as an excellent case study of the latent tensions that existed between single-service traditionalists and those committed to what was seen at the time as the “new way” in military organization.